The In Vivo and In Vitro Assessment of Pyocins in Treating Pseudomonas aeruginosa Infections - Abdulaziz Alqahtani; Jonathan Kopel; Abdul Hamood (MDPI AG, 2022)
Pseudomonas aeruginosa can cause several life-threatening infections among immunocompromised patients (e.g., cystic fibrosis) due to its ability to adapt and develop resistance to several antibiotics. In recent years, P. aeruginosa infections has become difficult to treat using conventional antibiotics due to the increase multidrug-resistant P. aeruginosa strains. Therefore, there is a growing interest to develop novel treatments against antibiotic-resistance P. aeruginosa strains. One novel method includes the application of antimicrobial peptides secreted by P. aeruginosa strains, known as pyocins. In this review, we will discuss the structure, function, and use of pyocins in the pathogenesis and treatment of P. aeruginosa infection.